Molecular pathogenesis, diagnosis, and management challenges in complete androgen insensitivity syndrome - Wang, Chunqing; Tian, Qinjie (Frontiers in Endocrinology, 2025)
Complete androgen insensitivity syndrome (CAIS) is a rare X-linked recessive disorder of sex development (DSD) caused by androgen receptor (AR) gene mutation and present with female phenotypes with male chromosomal karyotype. Primitive bipotent gonads in CAIS differentiate into testes producing androgens and antimüllerian hormone (AMH). However, androgens cannot stimulate embryonic wolffian ducts into male internal reproductive organs owing to AR defect and hormone resistance, while AMH induces the regression of müllerian ducts with the absence of uterus, fallopian tubes, and upper third of the vagina. Thus, with male sex chromosome and testes, individuals with CAIS present with a typical female phenotype, primary amenorrhea (PA) and infertility, spontaneous thelarche during puberty, absent or sparse axillary/pubic hair, and increased risk of gonadal tumors in cryptorchidism. Though theoretically CAIS can be screened prenatally through a discrepancy between chromosomal karyotype and fetal external genitalia, suspected in bilateral inguinal “hernia” cases with female genital phenotype, and considered in cases with elevated testosterone (T) levels but no signs of virilization, the lack of typical symptoms brings great challenges to diagnosis and management. Endocrinological hormone assay is helpful for the identification of CAIS which reveals normal or elevated T levels, elevated luteinizing hormone for impairment of negative feedback of T, and normal follicle-stimulating hormone which is regulated by both sex hormones and inhibin. The diagnosis of CAIS after puberty is similar to the diagnostic workflow of PA with additional tests and should be differentiated with PA-related etiologies and other kinds of DSD, such as Swyer syndrome, Mayer–Rokitanskey–Küster–Haüser syndrome, Leydig cell hypoplasia, and several steroidogenic enzymatic deficiencies. Clinical manifestations, hormonal profiles, chromosomal karyotype, and pelvic imaging can provide comprehensive information for diagnosis. AR gene test or binding capacity can be performed for definitive diagnosis. The management of CAIS includes gonadectomy, hormone supplementation, and psychological support and education. Although with the development of molecular biology and awareness of the clinical entity more cases were reported, diagnostic and management challenges exist due to the disease-related and treatment-related stress including the rarity, untypical clinical manifestations, increased risk of gonadal malignancy, and its influence on physiology and psychology. This review provides a comprehensive overview of the molecular pathogenesis, pathophysiology, diagnostic evaluation, differential diagnosis, and management of CAIS.